Facilitating software architecture - Harmel-Law, Andrew (O'Reilly Media, Inc., 2025)
The software architect role is evolving. As systems and distributed teams become more complex, it's often impossible for architects to be everywhere they need to be. To be effective, consultants and in-house architects alike have to move constantly from client to client or team to team to collaborate and work with code. And the situation is reaching a breaking point. There's a better way. Andrew Harmel-Law, tech principal at Thoughtworks, shows you how architects and development teams can collaborate effectively and efficiently on the architectures of their systems. Techniques in this book help you ensure that everyone and everything is working toward the same goal. You'll learn how to create a collaborative, decentralized mindset that allows everyone to do architecture and build the best systems they've ever experienced. With this book, you will: Understand the new dynamics that affect modern software delivery and how to take advantage of them to optimize for fast flow and continuous feedback Learn a methodology that brings software architecture and development together in partnership Nurture the fundamental interplay of decisions, advice, autonomy, and architecture Initiate practices and constraints that maximize benefits and mitigate risks Create an approach tuned to your skill sets, architecture, and your organization's engineering culture Identify and work to prevent failure modes when they threaten to arise.
Includes bibliographical references
Keywords: Software architecture; Software engineering; Architecture logicielle; Génie logiciel